The dual impact of digital integration and peer influence on smartphone addiction and psychological distress among Indonesian adolescents - Marthoenis Marthoenis; Julianti Jauhari (International Journal of Adolescent Medicine and Health, 2026)
Abstract Adolescents in higher health professional education experience heightened academic and clinical pressures, increasing their vulnerability to mental health problems. This study examined the prevalence of depression, anxiety, and stress, and identified key psychosocial predictors among Indonesian adolescents. A cross-sectional survey was conducted among 1,886 health polytechnic adolescents from multiple campuses of an Indonesian Health Polytechnic. Participants completed an online questionnaire including the Depression, Anxiety, and Stress Scale (DASS-21), alongside measures of self-esteem, mobile attachment, peer influence, and smartphone addiction. Multivariable linear regression was performed to identify predictors of psychological distress. Nearly half of the adolescents experienced moderate to extremely severe anxiety (48.9 %), followed by stress (30.7 %) and depression (25.4 %). Peer influence was the strongest protective factor, showing significant negative associations with depression (β=−0.352, p